Low programmed cell death‐1 (PD‐1) expression in peripheral CD4+ T cells in Japanese patients with autoimmune type 1 diabetes. (15th May 2015) - Fujisawa, R.; Haseda, F.; Tsutsumi, C.; Hiromine, Y.; Noso, S.; Kawabata, Y.; Mitsui, S.; Terasaki, J.; Ikegami, H.; Imagawa, A.; Hanafusa, T.
Summary Programmed cell death‐1 (PD‐1) is a co‐stimulatory molecule that inhibits T cell proliferation. We aimed to clarify PD‐1 expression in CD4+ T cells and the association between PD‐1 expression and the 7785C/T polymorphism of PDCD1, with a focus on the two subtypes of type 1 diabetes, type 1A diabetes (T1AD) and fulminant type 1 diabetes (FT1D), in the Japanese population. We examined 22 patients with T1AD, 15 with FT1D, 19 with type 2 diabetes (T2D) and 29 healthy control (HC) subjects. Fluorescence‐activated cell sorting (FACS) and real‐time PCR were utilized to analyse PD‐1 expression quantitatively. Genotyping of 7785C/T in PDCD1 was performed using the TaqMan method in a total of 63 subjects (21 with T1AD, 15 with FT1D and 27 HC). FACS revealed a significant reduction in PD‐1 expression in CD4+ T cells in patients with T1AD (mean: 4·2 vs. 6·0% in FT1D, P = 0·0450; vs. 5·8% in T2D, P = 0·0098; vs. 6·0% in HC, P = 0·0018). PD‐1 mRNA expression in CD4+ T cells was also significantly lower in patients with T1AD than in the HC subjects. Of the 63 subjects, PD‐1 expression was significantly lower in individuals with the 7785C/C genotype than in those with the C/T and T/T genotypes (mean: 4·1 vs. 5·9%, P = 0·0016). Our results indicate that lower PD‐1 expression in CD4+ T‐cells might contribute to the development of T1AD through T cell activation.